1219 INFORMAL CAREGIVERS OF PEOPLE WITH PARKINSONISM IN THE PRIME-UK CROSS-SECTIONAL STUDY. (16th January 2023) - Tenison, E; Cullen, A; Pendry-Brazier, D; Smith, M D; Ben-Shlomo, Y; Henderson, E J
Abstract: Introduction: Many people with parkinsonism require care as the disease progresses with much provided unpaid by family and friends. Caring for someone can have a negative impact on physical and psychosocial wellbeing. Caregiver burden can impact ability to continue this role, which can precipitate hospitalisation or institutionalisation of the recipient. Methods: In this single-site study, primary, informal caregivers, defined as those providing any care or support, were enrolled alongside the person with parkinsonism or individually. Self-reported questionnaires included the 22-item Zarit Burden Interview (ZBI), which can range from 0-88, with higher scores representing greater burden. Linear regression was used to explore the association between recipient characteristics/need and caregiver burden. Results: Of 1, 032 eligible patients approached, 813 participants indicated whether they had an informal caregiver (708) or not (105). 376 caregivers consented (53.1%), of whom 321 have returned questionnaires, with patient data available for 296. The median age of caregivers was 73.0 (range 27.0- 91.1 years), 237 (73.8%) female. 274 (85.4%) were the spouse/partner of the patient. 215 (67.0%) were the sole caregiver. The median time per week spent caring was 21 hours (interquartile range 7, 41 hours). 18 (5.6%) of caregivers provided 24-hour care daily and 113 (35.2%) had provided support for over 5 years. Median ZBI score was 17, (interquartile range 7-29). The care recipient's duration of parkinsonism was associated with higher burden score (0.38 increase per year of parkinsonism; 95% CI 0.07, 0.69; p value 0.015), as was the time per week spent caring (0.16 increase for each additional hour; 95% CI 0.11, 0.20; p value <0.0001). Conclusions: Many informal caregivers in this study were the sole caregiver and many were themselves older adults. Burden increased with increasing duration of parkinsonism and as time spent caring increased. This highlights the ongoing need to improve support for this group.